Cytomegalovirus Infections in Patients Treated With Immune Checkpoint Inhibitors for Solid Malignancies. (28th March 2023) - Anastasopoulou, Amalia; Samarkos, Michael; Diamantopoulos, Panagiotis; Vourlakou, Christina; Ziogas, Dimitrios C; Avramopoulos, Pantelis; Kouzis, Panagiotis; Haanen, John; Gogas, Helen
Abstract: Cytomegalovirus (CMV) infection/disease has been repeatedly reported in patients treated with immune-checkpoint inhibitors (ICIs) and most commonly involves patients with relapsed/refractory (R/R) immune-related adverse events (irAEs). In the current study, we present a patient with melanoma who developed CMV gastritis during treatment with pembrolizumab in the absence of irAEs and without previous or current immunosuppression. Moreover, we review the literature regarding CMV infection/disease in patients treated with ICIs for solid malignancies. We present the currently available data on the pathogenesis, clinical characteristics, endoscopic findings, and histologic features and highlight the potential differences among cases complicating R/R irAEs versus those occurring in patients who are immunosuppression naive. Finally, we discuss the currently available data regarding potential useful diagnostic tools as well as the management of these patients. Abstract : Herein, we present a case of CMV gastritis in a melanoma patient treated with pembrolizumab without previous or current use of immunosuppressants and review the literature for CMV infection/disease in patients with solid malignancies under treatment with immune checkpoint inhibitors.